LiNbO3 thin films prepared from a polymeric precursor method - Bouquet, V.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 1997)
LiNbO3 thin films were prepared from polymeric precursor method by dip coating. The precursor films, deposited on Si(111) substrates, were heat-treated from 400°C to 900°C in order to study the heat treatment influence on the crystallinity and microstructure of the final film. The X-ray diffraction patterns showed, in particular, that these films crystallize at low temperature (450°C) and present no preferential orientation. The scanning electron microscopy studies showed that the film microstructure is strongly influenced by the annealing temperature. © 1997 Trans Tech Publications.
Keywords: Ferroelectrics; Lithium niobate; Pechini; Thin films; Annealing; Crystal microstructure; Crystal orientation; Crystallization; Ferroelectric materials; Scanning electron microscopy; Semiconducting silicon; Substrates; X ray diffraction analysis; Polymeric precursor method; Lithium compounds